Magnetic properties of chiral EuIr2P2 - Garcia, Daniel Julio (2021)
We present a minimal model that provides a description of the magnetic and thermodynamic properties of EuIr2P2. The model contains two exchange coupling parameters, which are calculated using density functional theory, and a local easy-axis magnetic anisotropy term. The classical ground state of the system is a generalization of the well known 120 structure observed in triangular antiferromagnets. Monte Carlo simulations show two phase transitions as a function of the temperature. With increasing temperature, the system transitions from the ground state into a high-entropy collinear antiferromagnet, which in turn at higher temperatures presents a second-order transition to a paramagnetic state. A high enough external magnetic field parallel to the anisotropy axis produces a spin-flop transition at low temperatures. The field also reduces the temperature range of stability of the collinear antiferromagnet phase and leads to a single-phase transition as a function of the temperature. The reported behavior of the specific heat, the magnetization, and the magnetic susceptibility is in agreement with the available experimental data. Finally, we present the magnetic phase diagrams for magnetic fields parallel and perpendicular to the easy axis.